Reliability assessment of temporary structures using past performance information. (2015) - Mohammadi, Jamshid; Modares, Mehdi; Najafabadi, Aram Zare
Temporary structures are structural systems set up for applications in relatively short time periods for such functions as maintenance, repair or retrofit of a structure or for staged performances. This paper provides an overview of risk analysis models for temporary structures. In an attempt to provide a decision-making strategy for repeated usage of a given temporary structure, the performance record of a structure is used in predicting its future condition in the form of a probability of failure. This probability of failure is demonstrated as being a key factor in the decision-making process. To quantify the model, the special case of tube and coupler scaffolds is investigated. Considering stability requirement for a scaffold, gross capacity values are obtained for several configuration types. These capacity values are also important in computing the probability of failure of the systems and decision making in whether to allow the use of a system to continue.